Simple methods for identification of plastics - Braun, Dietrich (Hanser Publisher, 1999)
Plastics and their characteristics - General introduction to the analysis of plastics - Screening tests - Testing for heteroatoms - Analytical procedures - Specific identification tests - Specific plastics - Polymer blends - Detection of metals in polyvinyl chloride (PVC) - Advanced analytical methods - Appendix.